1979
DOI: 10.1161/01.res.44.6.752
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor control of atrioventricular conduction in man.

Abstract: Although human baroreflexes are known to exert a powerful physiological control on heart rate, little information exists on the physiological control they exert on the atrioventricular conduction system. In 11 normotensive subjects with normal atrioventricular conduction, we altered baroreceptor activity by injection of pressor and depressor drugs (phenylephrine and trinitroglycerin) and recorded mean arterial pressure (MAP, catheter measurements), R-R interval, and pre-His and post-His intervals (A-H and H-V,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…12 2) If the above modification of the baroreceptor reflex includes its powerful control of the atrioventricular node, 13 ANF might help depress arteriovenous conduction and terminate an episode of paroxysmal tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…12 2) If the above modification of the baroreceptor reflex includes its powerful control of the atrioventricular node, 13 ANF might help depress arteriovenous conduction and terminate an episode of paroxysmal tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…This can be inferred from the finding that from normotension to mild and more severe degrees of blood pressure elevation, there is a gradual reduction of the bradycardic and tachycardic responses to baroreceptor stimulation and deactivation, respectively (Figure 4, left), 41 a major mechanism of heart rate control. Because these responses are largely reduced, or even abolished, by the administration of atropine, 64 the mechanism is likely to be a progressive impairment of cardiac vagal modulation.…”
Section: Sympathetic Activation and Hypertension Severitymentioning
confidence: 99%
“…We previously have addressed this problem in humans by inducing physiological alterations in arterial baroreceptor activity while recording His bundle potentials and have concluded that a powerful vagal influence on atrioventricular conduction does operate normally. We have also observed, however, that this influence is complex, because it is exerted on some but not all portions of the atrioventricular conduction system and is modified to a large extent by concomitant alterations in cardiac cycle length (Mancia et al, 1979).…”
mentioning
confidence: 88%